Foreign capital inflows and welfare in an economy with imperfect competition. - Chao, Chi-Chur; Yu, Eden S. H. (Journal of Development Economics, 1994)
The writers consider the resource allocational and welfare effects of exogenous inflows of foreign capital in a general-equilibrium model with oligopolistic competition and unemployment. In the short run, the welfare impact is ambiguous and depends upon the strength of excess profits and scale economies relative to unemployment in manufacturing. However, in the long run, additional inflows of foreign capital always improve national welfare with capital mobility. Thus, attracting foreign capital remains a sound policy for economies that are characterized by imperfect competition, scale economies, and regional unemployment.